Bi-allelic truncating variants in CASP2 underlie a neurodevelopmental disorder with lissencephaly - Eyyup Uctepe (19342522) (2023)
Lissencephaly (LIS) is a malformation of cortical development due to deficient neuronal migration and abnormal formation of cerebral convolutions or gyri. Thirty-one LIS-associated genes have been previously described. Recently, biallelic pathogenic variants in CRADD and PIDD1, have associated with LIS impacting the previously established role of the PIDDosome in activating caspase-2. In this report, we describe biallelic truncating variants in CASP2, another subunit of PIDDosome complex. Seven patients from five independent families presenting with a neurodevelopmental phenotype were identified through GeneMatcher-facilitated international collaborations. Exome sequencing analysis was carried out and revealed two distinct novel homozygous (NM_032982.4:c.1156delT (p.Tyr386ThrfsTer25), and c.1174 C > T (p.Gln392Ter)) and compound heterozygous variants (c.[130 C > T];[876 + 1 G > T] p.[Arg44Ter];[?]) in CASP2 segregating within the families in a manner compatible with an autosomal recessive pattern. RNA studies of the c.876 + 1 G > T variant indicated usage of two cryptic splice donor sites, each introducing a premature stop codon. All patients from whom brain MRIs were available had a typical fronto-temporal LIS and pachygyria, remarkably resembling the CRADD and PIDD1-related neuroimaging findings. Other findings included developmental delay, attention deficit hyperactivity disorder, hypotonia, seizure, poor social skills, and autistic traits. In summary, we present patients with CASP2-related ID, anterior-predominant LIS, and pachygyria similar to previously reported patients with CRADD and PIDD1-related disorders, expanding the genetic spectrum of LIS and lending support that each component of the PIDDosome complex is critical for normal development of the human cerebral cortex and brain function. Other Information Published in: European Journal of Human Genetics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41431-023-01461-2